EVALUASI SISTEM PASSING GRADE DAN FAKTOR DISPARETAS ANTAR DAERAH DALAM SELEKSI CALON PEGAWAI NEGERI SIPIL (CPNS) - Matius Bangun; Adi Pradana (JURNAL RETENTUM, 2020)
ABSTRACT In recruiting candidates for Civil Servants (CPNS), the government issued several policies according to the problems and results of the evaluations carried out. Through the Passing Grade system the government strives to establish quality CPNS with the expected standards in accordance with the mandate of bureaucratic reform. But in reality the recruitment carried out with the Passing Grade as regulated in Permenpanpan-RB Number 37 of 2018 is not as expected where the average pass rate is below 10% and there are areas that do not pass at all or pass zero percent . This condition shows that in addition to the quality of human resources not as expected, there are also disvarites (gaps) that occur between regions, both provinces and districts / cities. The conclusion of this study is that the government has not been careful in measuring the level of quality of human resources, resulting in budget inefficiency in recruitment. The recommendation conveyed is that in addition to accuracy in measuring the quality of human resources, it can also take into account the disparities / disparities between regions as shown in the Index parameter.s Human Development (IPM).